2015
DOI: 10.1371/journal.pone.0123586
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Levels of High Mobility Group Box-1 Are Associated with Disease Activity in Antineutrophil Cytoplasmic Autoantibody-Associated Vasculitis

Abstract: BackgroundHigh mobility group box-1 (HMGB1), a kind of pro-inflammatory mediator, is associated with inflammatory conditions and tissue damage. Our previous study demonstrated that the circulating levels of HMGB1 correlated with disease activity of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). In the current study, we aimed to measure urinary levels of HMGB1 in AAV patients, correlated them to clinical activity index and analysed the immunohistochemical HMGB1 staining in kidney specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…[15] Ma et al study showed that urinary levels of HMGB1 may be associated with the disease activity in AAV patients. [29] This is similar to our results. However, de Souza et al found that HMGB1 levels were similar between AAV patients and HC and no significant differences were found regarding mean HMGB1 levels among AAV disease subsets.…”
Section: Discussionsupporting
confidence: 93%
“…[15] Ma et al study showed that urinary levels of HMGB1 may be associated with the disease activity in AAV patients. [29] This is similar to our results. However, de Souza et al found that HMGB1 levels were similar between AAV patients and HC and no significant differences were found regarding mean HMGB1 levels among AAV disease subsets.…”
Section: Discussionsupporting
confidence: 93%
“…It was found in our study that the levels of serum NGAL closely correlated with the Birmingham Vasculitis Activity Score as well as the level of erythrocyte sedimentation rate, C-reactive protein and ANCA [53]. Other biomarkers which could reflect the disease activity of AAV include circulating and urinary levels of high mobility group box-1, circulating levels of anti-plasminogen antibodies and circulating levels of D-dimer [54,55,56,57]. …”
Section: Outcomes Of Aav In Chinamentioning
confidence: 89%
“…In another AAV cohort [24], plasma levels of HMGB1 correlated with BVAS, serum creatinine, and eGFR, suggesting that circulating HMGB1 might reflect the disease activity and renal involvement of AAV. The same authors [25] reported increased urinary HMGB1 levels in active AAV patients, which correlated with disease activity. On the contrary, other studies found no difference regarding serum HMGB1 levels among AAV disease subsets and healthy controls [26].…”
Section: Discussionmentioning
confidence: 73%